Improving reliability and validity in hip-hop dance assessment: Judging standards that elevate the sport and competition - Sato, Nahoko (Frontiers in Psychology, 2022)
This study examined the reliability and validity of judging system scores of past hip-hop dance competitions in Japan. The analysis focused on the scores for each assessment category separately. Judges' scores were obtained from national dance competitions held annually in Japan between 2014 and 2019. In these competitions, five experienced judges evaluated the dancers’ performances. The judges scored on a 10-point scale in 5 categories as follows: creativity, expression and interpretation, impression, technical quality, and synchronisation. This study found that the technical quality category demonstrated good reliability, while impression showed poor reliability. Systematic bias was significant for all categories. There are no levels of difficulty defined for technique, no criteria set for correct movement, and no explanation provided for each scoring level, which suggests that each judge may have interpreted the criteria for evaluating hip-hop dance differently. Developing these definitions and identifying the biases that affect evaluation would ensure a reliable evaluation system.